PENGARUH SAYAP TERHADAP PERKECAMBAHAN BENIH MAHONI (Swietenia macrophylla King) ASAL BKPH CIANJUR KPH CIANJUR - Ika Nofi Hastuti (JAGROS : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science), 2017)
To produce a good quality Mahoni (Swietenia macrophylla King) tree, besides need a good sedds, also need a good source and a good treatment too.This research is interrelated with some test treatment, to get a good seedlings from the germination treatment , with saw the genetic expression from four treatment, the germination with full seeds, seeds with 50 % wings left, seeds with 25% wings left and seeds without wings. The genetic expression from each treatment showed by plant physologize process durung the germination, by seeds germination percentage parameters, quick of seeds germination , fast of seeds growth and seeds germination values. This four parameters has been analysis with complete random model. For quickest germination result is possessed by a seeds wihout wings, while fastest growth could be produced by a seeds with full wings.From the results of the analysis that each treatment showed a different genetic expression, seeds with 25% wings left have a high growth percentage and germination value than seeds without wings and seeds with full wings.But from all the treatment results, the best is possesessed by a seds with 25% wings left. Keyword : Wings, Seeds, Germ Mahoni (Swietenia macrophylla King).